ChemInform Abstract: Proper Ferroelectricity in the Dion—Jacobson Material CsBi2Ti2NbO10: Experiment and Theory. Issue 8 (February 2016) - McCabe, Emma E.; Bousquet, Eric; Stockdale, Christopher P. J.; Deacon, Charles A.; Tran, T. Thao; Halasyamani, P. Shiv; Stennett, Martin C.; Hyatt, Neil C.
Abstract: Polycrystalline CsBi2 Ti2 NbO10, an n = 3 member of the Dion—Jacobson (DJ) family, is prepared by solid state reaction of a stoichiometric mixture of Cs2 CO3, Bi2 O3, La2 O3, TiO2, and Nb2 O5 (alumina boat, 1.